2020
DOI: 10.1155/2020/6436102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Student Evaluation of Teaching (SET) Survey to Evaluate Effectiveness of Teaching in a Leadership Course among Dental Students over Three Years

Abstract: Leadership courses are being increasingly integrated into dental curricula. The study aimed to assess the validity and reliability of student evaluation of teaching (SET) instrument among dental students and to evaluate the effectiveness of teaching in a new leadership course over a period of three years. This cross-sectional study was conducted on fourth-year undergraduate dental students (N = 260) who took a practice management course over three consecutive years from 2014 to 2016. A 29-item SET questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In general, students have simple needs and focus on the obvious teaching traits when it comes to evaluating faculty members which include better teaching skills, responsiveness and openness to student feedback and suggestions, and commitment to class time and schedule. A study conducted amongst dental students found similar results [ 25 ]. Hence, with a myriad of factors being considered and valued by students, the basics of teaching, punctuality, and flexibility should not be forgotten and could be viewed as important areas for improvement.…”
Section: Discussionsupporting
confidence: 61%
“…In general, students have simple needs and focus on the obvious teaching traits when it comes to evaluating faculty members which include better teaching skills, responsiveness and openness to student feedback and suggestions, and commitment to class time and schedule. A study conducted amongst dental students found similar results [ 25 ]. Hence, with a myriad of factors being considered and valued by students, the basics of teaching, punctuality, and flexibility should not be forgotten and could be viewed as important areas for improvement.…”
Section: Discussionsupporting
confidence: 61%
“…These comparisons of students’ learning provide opportunities to assess improvement over successive years and are crucial to ensuring the quality and effectiveness of the course. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The teaching effectiveness questionnaire had a total of 27 items [21]. It had four indicators, namely: assessment and evaluation (1-13), interaction with students (1-5), teaching and learning (1-7), preparedness of teachers (1)(2)(3)(4).…”
Section: Research Instrumentsmentioning
confidence: 99%